Pharmacological Isolation of Cognitive Components Influencing the Pupillary Light Reflex - Stuart R. Steinhauer; Ruth Condray; Misha L. Pless (Journal of Ophthalmology)
Cognitive operations can be detected by reduction of the pupillary light response. Neurophysiological pathways mediating this reduction have not been distinguished. We utilized selective blockade of pupillary sphincter or dilator muscles to isolate parasympathetic or sympathetic activity during cognition, without modifying central processes. Pupil diameter was measured during the light reaction in 29 normal adults under three processing levels: No Task, during an easy task (Add 1), or a difficult task (Subtract 7). At three separate sessions, the pupil was treated with placebo, tropicamide (blocking the muscarinic sphincter receptor), or dapiprazole (blocking the adrenergic dilator receptor). With placebo, pupil diameter increased with increasing task difficulty. The light reaction was reduced only in the Subtract 7 condition. Dapiprazole (which decreased overall diameter) showed similar task-related changes in diameter and light reflex as for placebo. Following tropicamide (which increased overall diameter), there was a further increase in diameter only in the difficult task. Findings suggest two separate inhibitory components at the parasympathetic oculomotor center. Changes in baseline diameter are likely related to reticular activation. Inhibition of the light reaction in the difficult task is likely associated with cortical afferents. Sustained sympathetic activity also was present during the difficult task.